Gerakan Menuju Sekolah Adiwiyata: Pendampingan Program Peduli dan Berbudaya Lingkungan Hidup Sekolah di Kabupaten Malang - Tuti Mutia; Eli Hendrik Sanjaya; Novika Adi Wibowo; Melati Julia Rahma; Mohd Hairy Ibrahim (Jurnal Pemberdayaan Masyarakat, 2026)
Environmentally conscious character development can be encouraged through environmental education, which provides an understanding of the importance of protecting and preserving nature. One example of environmental education in Indonesia is the Adiwiyata program, which aims to instill environmental values ​​in students from an early age. By focusing on the development of the Environmental Care and Culture Movement in Schools (PBLHS), Adiwiyata pilot schools can play an active role in building students' awareness and skills to apply the principles of sustainability and good environmental management in their daily lives. This community service activity aims to provide mentoring to teachers and school officials in the development and implementation of PBLHS integrated into the school curriculum and culture. Using a Participatory Action Research (PAR) approach, this activity is carried out through several stages, including preparation, implementation, evaluation, and sustainability. The target of this service is 50 Adiwiyata pilot elementary schools in Malang Regency. The results of this community service demonstrate that Adiwiyata pilot schools are able to develop and develop PBLHS programs tailored to the unique characteristics and needs of each school, thereby creating a sustainable school environment. This program is expected to have a positive impact on the development of environmental education.